A mathematical approach to special relativity - Shariati, Ahmad (Academic Press, 2022)
A Mathematical Approach to Special Relativity introduces the mathematical formalisms of special and general relativity. Developed from the author's experience teaching physics to students across all levels, the valuable resource introduces key concepts, building in complexity and using increasingly advanced mathematical tools as it progresses. Without assuming a background in calculus, the text begins with symmetry, before delving more deeply into Galilean relativity. Throughout, the book provides examples and useful "Guides to the Literature." This unique text emphasizes the experimental consequences and verifications of the underpinning theory in order to provide students with a solid foundation in this key area.